Synergistic effects of strontium carbonate on a novel intumescent flame‐retardant polypropylene system. (11th April 2021) - Chen, Kui; Cheng, Jingwei; Wu, Bin; Liu, Chengjuan; Guo, Jianing
Abstract : The effect of a synergistic flame‐retardant system with epoxy resin microcapsule modified ammonium polyphosphate (MAPP) as the primary flame retardant, and strontium carbonate (SrCO3 ) as the synergistic agent on the flame retardancy of polypropylene (PP) were studied. The flame‐retardant performance of the prepared PP composite samples was analyzed by vertical combustion test (UL94), limiting oxygen index (LOI) test, cone calorimeter test, infrared chromatography (FT‐IR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and other technical means. The results showed that when the addition amount of SrCO3 was 1.5 wt%, the LOI reached 36.1%, and the UL‐94 test reached V‐0. Compared with no SrCO3 added sample, the peak heat release rate (PHRR) dropped from 395 to 378 kW/m 2 . The SEM data showed that the addition of SrCO3 enabled the flame‐retardant system to form a firmer char layer. The TGA data showed that SrCO3 catalyzes the MAPP reaction to form a cross‐linked structure and forms a bridge bond between the two phosphate groups to promote a stable carbon layer. Compared with no SrCO3 added sample, PP composite's tensile strength was increased from 26.78 to 29.42 MPa. Thus, a suitable amount of SrCO3 had a synergistic effect on the flame retardancy of the PP composite and had improved the system's mechanical properties.